2021
DOI: 10.37349/etat.2021.00053
|View full text |Cite
|
Sign up to set email alerts
|

A novel strategy for treating cancer: understanding the role of Ca2+ signaling from nociceptive TRP channels in regulating cancer progression

Abstract: Cancer is an aging-associated disease and caused by genomic instability that is driven by the accumulation of mutations and epimutations in the aging process. Although Ca2+ signaling, reactive oxygen species (ROS) accumulation, DNA damage response (DDR) and senescence inflammation response (SIR) are processed during genomic instability, the underlying mechanism for the cause of genomic instability and cancer development is still poorly understood and needs to be investigated. Nociceptive transient receptor pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 120 publications
0
7
0
Order By: Relevance
“…Calcium signals are central in the mechanisms underlying cancer cell proliferation, death and migration ( 1 ). Therefore, TRPC7 may promote cancer development and TRPC6 or other TRP channels cannot be excluded from roles in the regulation of cancer development through Ca 2+ /CaMKII/AKT and/or Ca 2+ /CaMKII/ERK axes ( 5 ). Furthermore, cell proliferation results of the present study only demonstrated the significance at Day 2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Calcium signals are central in the mechanisms underlying cancer cell proliferation, death and migration ( 1 ). Therefore, TRPC7 may promote cancer development and TRPC6 or other TRP channels cannot be excluded from roles in the regulation of cancer development through Ca 2+ /CaMKII/AKT and/or Ca 2+ /CaMKII/ERK axes ( 5 ). Furthermore, cell proliferation results of the present study only demonstrated the significance at Day 2 ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…6 ). There are an increasing number of TRP channels that have been reported to promote cancer development and Ca 2+ /CaMKII has emerged as a crucial signaling pathway in the modulation of cell proliferation, the cell cycle, invasion and metastasis, and therapy efficacy in cancer ( 5 ). For example, TRPV4 promotes oral squamous cell carcinoma cell proliferation via activation of the Ca 2+ /CaMKII/AKT axis ( 19 ) and TRPM7 mediates breast cancer cell migration and invasion via the CaMKII-dependent MAPK signaling pathway ( 20 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[16,17] H 2 has emerged as a promising therapeutic option for oxidative stress-related diseases, including AD, [18,19] owing to its ability to attenuate ROS and inflammatory responses. [20] In recent years, the in situ photocatalytic H 2 production of semiconductor nanomaterials has garnered widespread attention. The underlying principle is that when a semiconductor absorbs photons, valence band electrons become excited to the conduction band, leaving behind holes (h + ).…”
Section: Introductionmentioning
confidence: 99%